2015
DOI: 10.1007/s10661-015-4883-x
|View full text |Cite
|
Sign up to set email alerts
|

Sewage-fed aquaculture: a sustainable approach for wastewater treatment and reuse

Abstract: This study assesses the long-term sustainability for operation and maintenance (O&M) of sewage-fed aquaculture-based sewage treatment system. The study focused on the integrated assessment of an engineered pond system of 8 million liters per day capacity in the city of Karnal, the State of Haryana, northern India. Major areas during the assessment included health, environmental, societal and institutional views aspects as well as the quality of treated effluent subjected for reuse. The treatment facility met t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 30 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…The United Nations estimates that by 2025 two-thirds of the world population will likely be under water stress [ 18 ]. For other water-intensive activities there has been increasing interest in many parts of the world in treating and recycling wastewater, including crop irrigation [ 19 ], fish culture [ 20 ] and aquatic macrophyte production [ 21 ]. The option of re-using water to rear successive generations of mosquito larvae is likewise attractive to reduce water usage and running costs, and help to make the SIT viable.…”
Section: Introductionmentioning
confidence: 99%
“…The United Nations estimates that by 2025 two-thirds of the world population will likely be under water stress [ 18 ]. For other water-intensive activities there has been increasing interest in many parts of the world in treating and recycling wastewater, including crop irrigation [ 19 ], fish culture [ 20 ] and aquatic macrophyte production [ 21 ]. The option of re-using water to rear successive generations of mosquito larvae is likewise attractive to reduce water usage and running costs, and help to make the SIT viable.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages for the treatment plant operator are the possibility of cost savings and recovery through leasing the ponds and/or asking the farmer to arrange for the maintenance of the pond system. From a public sector perspective, leasing ponds to farmers or sale of fish, aquatic plants and/or irrigation water 1 represent interesting opportunities to offset at least the operational costs of wastewater treatment, if not the capital costs, as shown in India and Bangladesh for example (Kumar et al 2015;.…”
Section: Wastewater Aquaculture As a Business Modelmentioning
confidence: 99%
“…66 Heberer et al, demonstrated that whilst bank ltration can decrease the concentration of certain pharmaceuticals (dilution and/or removal) pharmaceutically active substances are still present in sampled ground waters at bank ltration sites. 67 Similarly, the use of reclaimed wastewater to support aquaculture is known to be practiced 68 although we have limited understanding of the specic locations and volumes of water used which presents a challenge with regards to quantifying the presence of pharmaceuticals in these systems (Fig. 1; pathway 7).…”
Section: Consumption Of Surface Water By Wildlife and Livestockmentioning
confidence: 99%